Hedonism of Jazz Era Society in The Characters of The Short Story “The Diamond as Big as The Ritz” - Alawiyah, Siti Dilla; Nurholis, Nurholis (English Language and Literature, 2024)
Literary works can raise social stories, namely stories that describe the conditions, problems, and social dynamics of society in a certain period. This study aims to describe the hedonistic lifestyle of American society in the jazz era of the 1920s, as reflected in the characters of the short story The Diamond as Big as the Ritz by Scott Fitzgerald. This research method uses qualitative data. The data source for this study is the hedonistic behavior of the Washington family characters, who are full of luxury and greed through the narrative in the short story. The results of this study show that in this short story there is a reflection of the hedonistic lifestyle of American society in the jazz era. Among them are material luxury, loss of social morals, prioritizing personal interests at all costs, and alcohol addiction as a form of self-satisfaction, as well as the impact of hedonism, namely discrimination against negro.